Alterações na estabilidade de agregados de latossolo e argissolo em função do manejo, na entrelinha da seringueira (Hevea brasiliensis) - Ribon, Adriana Aparecida; Centurion, José Frederico [UNESP]; Pessoa da Cruz Centurion, Maria Aparecida [UNESP]; Fernandes, Kathleen Lourenco; Lourenceti Hermogenes, Victor Talles (Univ Federal Viçosa, 2014)
A trial was carried out with the purpose of evaluating the effect of different management systems applied between the rows of rubber trees (Hevea brasiliensis) on the aggregate stability in water of Dark Red Latosol, with clayey texture from the Municipality of Jaboticabal (SP) and Yellow Red Podzolic, sandy?medium texture fromthe Municipality of Tabapuã (SP). The treatments consisted of disk harrowing, Pueraria phaseoloides and mowing. The soil samples were withdrawn after seven years of application of these management systems from depths of 0-0.1, 0.1-0.2, 0.2-0.3, and 0.3-0.4 m. The stability of the aggregates was obtained in sieves with size classes of 8-4, 4-2, 2-1, 1-0.5, 0.5-0.125, and <0.125 mm. The Pueraria phaseoloides gave a significant difference regarding the distribution of the aggregates on the superficial layer (10 cm) when compared to the other management systems, presenting a higher distribution of larger sized aggregates on the Dark Red Latosol. The tillage management for this same depth presented higher values of small sized aggregates on both soils. The organic matter on the soils showed a direct and significant relation to the stability of the larger sized aggregates and an inverse relation with the stability of the smaller sized aggregates.
Changes in the aggregate stability of Latosol and podzolic according to the management between the rows of rubber trees (Hevea brasiliensis)
Keywords: Aggregate stability; Handling; Rubber tree; Estabilidade de agregados; Manejo; Seringueira